ลักษณะการทำงานและบทบาทของล่ามในสำนักข่าวกรองแห่งชาติ - กรพิม วุฒิวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This article aims to study the working condition and role of interpreters in the National Intelligence Agency, the Prime Minister s Office. The objectives of this study cover the demand, working condition and role of the interpreters, including related problems and solutions. This research is conducted by interviewing relevant personnel in policy and operational level, which are the Director and interpreters of the National Intelligence Agency: 3 interpreters by position and 20 civil servants who work as interpreters. It was found that language officers with skills in languages of neighboring countries to Thailand are wanted the most. Their work includes translation and interpretation which is mostly consecutive interpretation. The problems found were the lack of career stability, interpreter skill training and foreign language education. Therefore, relevant agencies should give importance and support the National Intelligence Agency in creating language expert positions to solve problems of work, improve benefits appropriately and set up training courses to improve language officers quality.